Sheep and Goats Respond Differently to Feeding Strategies Directed to Improve the Fatty Acid Profile of Milk Fat - Anna Nudda; Antonello Cannas; Fabio Correddu; Alberto Stanislao Atzori; Mondina Francesca Lunesu; Gianni Battacone; Giuseppe Pulina (Animals, 2020)
This bibliographic review presents and discusses the nutritional strategies able to increase the concentration of beneficial fatty acids (FA) in sheep and goat milk, and dairy products, with a particular focus on the polyunsaturated FA (PUFA), and highlights differences between the two species. In fact, by adopting appropriate feeding strategies, it is possible to markedly vary the concentration of fat in milk and improve its FA composition. These strategies are based mostly on the utilization of herbage rich in PUFA, or on the inclusion of vegetable, marine, or essential oils in the diet of lactating animals. Sheep respond more effectively than goats to the utilization of fresh herbage and to nutritional approaches that improve the milk concentration of c9,t11-conjugated linoleic acid (c9,t11-CLA) and α-linolenic acid. Dietary polyphenols can influence milk FA profile, reducing or inhibiting the activity and growth of some strains of rumen microbes involved in the biohydrogenation of PUFA. Although the effectiveness of plant secondary compounds in improving milk FA composition is still controversial, an overall positive effect has been observed on the concentration of PUFA and RA, without marked differences between sheep and goats. On the other hand, the positive effect of dietary polyphenols on the oxidative stability of milk fat appears to be more consistent.